2016
DOI: 10.1021/acs.jpcb.6b08059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Skin Lipids: Effect of Ceramide Chain Lengths on Bilayer Properties

Abstract: Stratum corneum (SC), the outer layer of skin, serves as a barrier for pathogens and maintains the trans-epidermal water loss. The lipid matrix of SC is the major diffusion-rate-limiting pathway as molecules will have to pass through it. Ceramides play a key role in structuring and maintaining the barrier function of the skin. In this study, atomistic molecular dynamics (MD) simulations were used to systematically investigate the effects of the chain length of ceramide (CER) tails on the properties of the bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 72 publications
1
64
0
Order By: Relevance
“…The free energy profile shows no barrier in the interior of the bilayer for neutral hydrophobic AuNPs so diffusion controlled the permeability. Similar phenomena has also been reported earlier for hydrophobic nanoparticle and hydrophobic molecules permeation through bilayer2954. The free energy for each AuNP in the interior of the bilayer was negative (energetically favorable) but the diffusion coefficients decreased significantly with increasing size.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The free energy profile shows no barrier in the interior of the bilayer for neutral hydrophobic AuNPs so diffusion controlled the permeability. Similar phenomena has also been reported earlier for hydrophobic nanoparticle and hydrophobic molecules permeation through bilayer2954. The free energy for each AuNP in the interior of the bilayer was negative (energetically favorable) but the diffusion coefficients decreased significantly with increasing size.…”
Section: Resultssupporting
confidence: 87%
“…The independency of diffusion to permeate size, in the bilayer interior, as compared to the water, was previously reported57, and relatively constant values along with the bilayer normal were previously reported for a nifedipine drug analog58. However, the diffusion constant values of the small molecular permeates changed with respect to z, and it has been correlated to membrane heterogeneity (differences in free volume)545557. The diffusion values were found to be higher for smaller AuNP as compared to larger nanoparticles.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Additionally, ceramides (CERs) are synthesised in the endoplasmic reticulum of the keratinocytes, and their anisometric molecular structure differs markedly from other lipid classes [15,16]. Due to load differences within their long-chain molecules, CERs are able to spontaneously form lyotropic mesophases (also known as liquid-crystalline membrane structures) [17,18]. Unlike phospholipids, functionally important CERs in the SC contain 2 alkyl chains of different lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to study the biophysical properties of key lipid components with a single bilayer for the CHARMM36 and GROMOS force fields. 52,[110][111][112][113][114][115][116][117][118][119][120] Many have focused on using three-lipid models of a ceramide, fatty acid, and cholesterol to mimic the SC. Moore et al 110 found that bilayer thickness depends strongly on the level of tail-length asymmetry and permeability strongly depends on tail-length variation.…”
Section: Example All-atom/united-atom Cell Membrane Modelsmentioning
confidence: 99%